Effectiveness of a specific care plan in patients with Alzheimer's disease: cluster randomised trial (PLASA study) - Fati Nourhashémi; Sandrine Andrieu; Sophie Gillette‐Guyonnet; Bruno Giraudeau; Christelle Cantet; Nicola Coley; Bruno Vellas (2010)
Elevated PGE2 is a hallmark of most inflammatory lesions. This lipid mediator can induce the cardinal signs of inflammation, and the beneficial actions of nonsteroidal anti-inflammatory drugs are attributed to inhibition of cyclooxygenase (COX)-1 and COX-2, enzymes essential in the biosynthesis of PGE2 from arachidonic acid. However, both clinical studies and rodent models suggest that, in the asthmatic lung, PGE2 acts to restrain the immune response and limit physiological change secondary to inflammation. To directly address the role of PGE2 in the lung, we examined the development of disease in mice lacking microsomal PGE2 synthase-1 (mPGES1), which converts COX-1/COX-2–derived PGH2 to PGE2. We show that mPGES1 determines PGE2 levels in the naive lung and is required for increases in PGE2 after OVA-induced allergy. Although loss of either COX-1 or COX-2 increases the disease severity, surprisingly, mPGES1−/− mice show reduced inflammation. However, an increase in serum IgE is still observed in the mPGES1−/− mice, suggesting that loss of PGE2 does not impair induction of a Th2 response. Furthermore, mPGES1−/− mice expressing a transgenic OVA-specific TCR are also protected, indicating that PGE2 acts primarily after challenge with inhaled Ag. PGE2 produced by the lung plays the critical role in this response, as loss of lung mPGES1 is sufficient to protect against disease. Together, this supports a model in which mPGES1-dependent PGE2 produced by populations of cells native to the lung contributes to the effector phase of some allergic responses.